Proses Pembelajaran Di Rumah Untuk Anak Usia Dini Di Masa Pandemi Covid-19 - Rozana, Salma (Jurnal Ilmiah Al-Hadi, 2023)
This paper aims to describe the learning process at home for early childhood during the covid-19 pandemic in PAUD or kindergarten located in Bahorok village, Langkat District, North Sumatra. This research uses inductive qualitative research. This research was conducted for kindergarten or early childhood teachers who are members of HIMPAUDI in the Bahorok village. Data collection techniques used in this study are interviews, observations, and documentation studies. Data analysis techniques used in this study using qualitative descriptive analysis techniques. Based on the results of interviews and observations, there are still many obstacles experienced by parents and teachers in giving assignments and teaching children via online.